Dynamique spatio temporelle de l’agriculture urbaine à Ouagadougou : Cas du Maraîchage comme une activité montante de stratégie de survie - Conchita M. G. Kêdowidé; Michel P. Sedogo; Guéladio Cissé (VertigO)
The present study characterizes the different types of urban agriculture in Ouagadougou and defines their spatial distribution. The study was specifically interested in the spatial and temporal dynamics for more than a decade. The first studies on truck farming in Ouagadougou took place in 1992 with a spatial inventory in 1996 which also corresponds to the period when the agrarian and land Reform was adopted in Burkina (RAF stands for Réforme Agraire et Foncière). The RAF does not explicitly prevent urban agriculture within the city of Ouagadougou, rather it says that the urban fields of Burkina are mainly used for activities related to the needs of the urban life (housing, trade, industry, arts crafts), while rural fields are mainly for agriculture, cattle breeding (or livestock), and to other rural activities in general. This reason justifies the relevant choice of this year as reference in the analysis of this spatial dynamics. The results present the spatial distribution of the sites of agriculture in the city of Ouagadougou between 1996 and 2009, as well as the total surface area exploited in the truck farming according to the seasons. They analyze the spatial and temporal dynamics observed according to the urban land pressure and to the availability of the water, which is an indispensable resource for the survival of the activity. Therefore, this is an inexplicit prohibition which exists since then, which explains the pertinent choice of 1996 as the reference in the analysis of the spatial evolution of this activity. The results present the spatial distribution of the sites of agriculture in the city of Ouagadougou between 1996 and 2009, as well as the total surface area exploited in the truck farming according to the seasons. They analyze the spatial and temporal dynamics observed according to the urban land pressure and to the availability of the water, which is an indispensable resource for the survival of the activity.